2016
DOI: 10.1111/eip.12315
|View full text |Cite
|
Sign up to set email alerts
|

Relation between premorbid adjustment, duration of untreated psychosis and close interpersonal trauma in first‐episode psychosis

Abstract: Close interpersonal trauma before the age of 18 is associated with poorer premorbid adjustment and a longer duration of untreated psychosis. This may indicate that traumatic experiences delay help-seeking behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…CHR and PD participants also reported more direct, interpersonal forms of PTEs (ie, Sexual Abuse , Physical Abuse , Victim of a Violent Crime ) relative to TD participants. While larger samples sizes are necessary to examine specific types of trauma as they relate to psychosis risk, these results align with previous work highlighting the strong association between interpersonal traumatic events and the development of psychotic symptoms, particularly among victims who maintain a close relationship with the perpetrator (Gibson, Alloy, & Ellman, ; Haahr et al, ). Among the CHR group, 63.2% reported at least 1 previous PTE, less than the 86.8% found in Kraan et al's meta‐analysis ().…”
Section: Discussionsupporting
confidence: 86%
“…CHR and PD participants also reported more direct, interpersonal forms of PTEs (ie, Sexual Abuse , Physical Abuse , Victim of a Violent Crime ) relative to TD participants. While larger samples sizes are necessary to examine specific types of trauma as they relate to psychosis risk, these results align with previous work highlighting the strong association between interpersonal traumatic events and the development of psychotic symptoms, particularly among victims who maintain a close relationship with the perpetrator (Gibson, Alloy, & Ellman, ; Haahr et al, ). Among the CHR group, 63.2% reported at least 1 previous PTE, less than the 86.8% found in Kraan et al's meta‐analysis ().…”
Section: Discussionsupporting
confidence: 86%
“…Of all the variables investigated, poor premorbid adjustment was significantly associated with male gender. Studies 14 , 45 , 46 , 47 have shown that males with schizophrenia tend to have poorer premorbid functioning than their female counterparts. Other authors 19 have also posited that males experience more decline in their premorbid functioning over the epoch ages.…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration of untreated psychosis (DUP) has also been linked to poorer medium-long term outcomes (Marshall et al, 2005), though a recent meta-analysis suggests that correlations are small and leave substantial variability unexplained (Penttilä, Jääskeläinen, Hirvonen, Isohanni, & Miettunen, 2014). Childhood trauma and community disadvantage have also been strongly linked not only to increased risk for developing psychosis but also to initial help-seeking pathways and outcomes following onset (Cotter, Kaess, & Yung, 2015;Haahr et al, 2016;Stain et al, 2014). Outcomes and engagement in services are strongly linked, and a recent meta-analysis of engagement predictors found consistent evidence for DUP, symptom severity, insight, substance abuse and family involvement (Doyle et al, 2014).…”
mentioning
confidence: 99%